Regime-switching Volatility of Stock Returns and Exchange Rates in Latin - Tovar-Silos, Ricardo (Journal of Applied Business and Economics, 2017)
A SWARCH model was applied to the stock returns and exchange rates of Brazil, Chile and Mexico. Two volatility states are present and the high volatility periods were identified and dated. The length of the high volatility period was greater for stock returns during the financial crises of the nineties whereas during the global financial crisis exchange rates experienced a longer period of high volatility. The European sovereign debt crisis and the end of the Fed’s QE program caused high volatility on the exchange rates only. The degree of concordance between the high volatility regimes of stock returns and exchange rates is low in the three countries and only Brazil reported a significant positive correlation between the states.